2017
DOI: 10.2147/jir.s141682
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin-6/6R gene polymorphisms and coronary artery disease in Russian population: influence of interleukin-6/6R gene polymorphisms on inflammatory markers

Abstract: This study determined the genotype effects of interleukin (IL)-6/IL-6R single nucleotide polymorphisms (SNPs) on circulating levels of different cytokines in healthy and coronary artery disease (CAD) patients with different allele frequencies. In the control patients, rs1800795 showed significant differences in IL-18 concentrations between CC and CG and CC and GG genotypes (P=0.003 and 0.004, respectively). Furthermore, circulatory IL-1β was significantly different between GC and GG genotypes from the same SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…After excluding the overlapping articles of the literature search and applying the selection criteria mentioned previously, 74 research articles (Coker et al, 2011[ 14 ]; Banerjee et al, 2008[ 3 ], 2009[ 4 ]; Balding et al, 2004[ 2 ]; Bennet et al, 2003[ 7 ]; Akinyemi et al, 2017[ 1 ]; Humphries et al, 2001[ 31 ], 2007[ 30 ]; Jabir et al, 2017[ 33 ]; Jenny et al, 2002[ 34 ]; Elsaid et al, 2014[ 17 ]; Chiappelli et al, 2005[ 13 ]; Flex et al, 2004[ 20 ]; Karahan et al, 2005[ 37 ]; Li et al, 2015[ 41 ]; Liaquat et al, 2014[ 42 ]; Kelberman et al, 2004[ 38 ]; Kou et al, 2017[ 39 ]; Lalouschek et al, 2006[ 40 ]; Satti et al, 2013[ 63 ]; Sekuri et al 2007[ 64 ]; Sie et al, 2006[ 65 ]; Wang et al, 2015;[ 81 ] Weger et al, 2005[ 82 ]; Yang et al, 2015[ 83 ]; Basso et al, 2002[ 5 ]; Bennermo et al, 2011[ 6 ]; Berg et al, 2009[ 8 ]; Bhanushali et al, 2013[ 9 ]; Buraczynska et al, 2016[ 10 ]; Chakraborty et al, 2013[ 11 ]; Chamorro et al, 2005[ 12 ]; Danielsson et al, 2005[ 15 ]; Densem et al, 2005[ 16 ]; Fan et al, 2011[ 18 ]; Flex et al, 2002[ 21 ]; Galimudi et al, 2014[ 22 ]; George et al, 2004[ 23 ]; Georges et al, 2001[ 24 ]; Ghazouani et al, 2010[ 26 ], 2011[ 25 ]; Greisenegger et al, 2003[ 27 ]; Hongmei et al, 2016[ 28 ]; Jun et al, 2017[ 36 ]; Licastro et al, 2004[ 43 ]; Lieb et al, 2004[ 44 ]; Maitra et al, 2008[ 48 ]; Mao et al, 2016[ 49 ]; Mastana et al, 2017[ 50 ]; Mishra et al, 2013[ 51 ]; Mitrokhin et al, 2017[ 52 ]; Myśliwska et al, 2006[…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding the overlapping articles of the literature search and applying the selection criteria mentioned previously, 74 research articles (Coker et al, 2011[ 14 ]; Banerjee et al, 2008[ 3 ], 2009[ 4 ]; Balding et al, 2004[ 2 ]; Bennet et al, 2003[ 7 ]; Akinyemi et al, 2017[ 1 ]; Humphries et al, 2001[ 31 ], 2007[ 30 ]; Jabir et al, 2017[ 33 ]; Jenny et al, 2002[ 34 ]; Elsaid et al, 2014[ 17 ]; Chiappelli et al, 2005[ 13 ]; Flex et al, 2004[ 20 ]; Karahan et al, 2005[ 37 ]; Li et al, 2015[ 41 ]; Liaquat et al, 2014[ 42 ]; Kelberman et al, 2004[ 38 ]; Kou et al, 2017[ 39 ]; Lalouschek et al, 2006[ 40 ]; Satti et al, 2013[ 63 ]; Sekuri et al 2007[ 64 ]; Sie et al, 2006[ 65 ]; Wang et al, 2015;[ 81 ] Weger et al, 2005[ 82 ]; Yang et al, 2015[ 83 ]; Basso et al, 2002[ 5 ]; Bennermo et al, 2011[ 6 ]; Berg et al, 2009[ 8 ]; Bhanushali et al, 2013[ 9 ]; Buraczynska et al, 2016[ 10 ]; Chakraborty et al, 2013[ 11 ]; Chamorro et al, 2005[ 12 ]; Danielsson et al, 2005[ 15 ]; Densem et al, 2005[ 16 ]; Fan et al, 2011[ 18 ]; Flex et al, 2002[ 21 ]; Galimudi et al, 2014[ 22 ]; George et al, 2004[ 23 ]; Georges et al, 2001[ 24 ]; Ghazouani et al, 2010[ 26 ], 2011[ 25 ]; Greisenegger et al, 2003[ 27 ]; Hongmei et al, 2016[ 28 ]; Jun et al, 2017[ 36 ]; Licastro et al, 2004[ 43 ]; Lieb et al, 2004[ 44 ]; Maitra et al, 2008[ 48 ]; Mao et al, 2016[ 49 ]; Mastana et al, 2017[ 50 ]; Mishra et al, 2013[ 51 ]; Mitrokhin et al, 2017[ 52 ]; Myśliwska et al, 2006[…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1 (Tab. 1) (References in Table 1: Akinyemi, 2017[ 1 ]; Balding, 2004[ 2 ]; Banerjee, 2008[ 3 ]; Basso, 2002[ 5 ]; Bennermo, 2011[ 6 ]; Bennet, 2003[ 7 ]; Berg, 2009[ 8 ]; Bhanushali, 2013[ 9 ]; Buraczynska, 2016[ 10 ]; Chakraborty, 2013[ 11 ]; Chamorro, 2005[ 12 ]; Chiapelli, 2005[ 13 ]; Coker, 2011[ 14 ]; Danielsson, 2005[ 15 ]; Densem, 2005[ 16 ]; Elsaid, 2014[ 17 ]; Fan, 2011[ 18 ]; Flex, 2002[ 21 ]; Flex, 2004[ 20 ]; Flex, 2007[ 19 ]; Galimudi, 2014[ 22 ]; George, 2004[ 23 ]; Georges, 2001[ 24 ]; Ghazouani, 2010[ 26 ]; Ghazouani, 2011[ 25 ]; Greisenegger, 2003[ 27 ]; Hongmei, 2016[ 28 ]; Humphries, 2001[ 31 ]; Humphries, 2007[ 30 ]; Jabir, 2017[ 33 ]; Jenny, 2002[ 34 ]; Jun, 2017[ 36 ]; Karahan, 2005[ 37 ]; Kelberman, 2004[ 38 ]; Kou, 2017[ 39 ]; Lalouschek, 2006[ 40 ]; Li, 2015[ 41 ]; Liaquat, 2014[ 42 ]; Licastro, 2004[ 43 ]; Lieb, 2004[ 44 ]; Maitra, 2008[ 48 ]; Mao, 2016[ 49 ]; Mastana, 2017[ 50 ]; Mishra[ 51 ], 2013; Mitrokhin, 2017[ 52 ]; Mysliwska, 2006[ 53 ]; Nauck, 2002[ 54 ]; Panoulas, 2009[ 55 ]; Phulukdaree, 2013[ 56 ]; Potacsek, 2007[ 57 ]; Revilla, 2002[ 58 ]; Rios, 2010[ 59 ]; Rosner, 2005[ 60 ]; Salama, 2015[ 61 ]; Sarecka, 2008[ 62 ]; Satti, 2013[ 63 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation of sample size and baseline characteristics of the patients are given in details in our previous study. 13 Briefly, the district demographic data from the 2012 Census, with a population of 507,000 inhabitants were taken for sample size computation. Assuming a 10% margin of error and a maximum prevalence of 50%, with a 95% CI, a sample minimum was defined at 126 participants (cases).…”
Section: Methodsmentioning
confidence: 99%
“…Coronary heart disease (CHD), also known as coronary artery disease (CAD), is one of the leading causes of death worldwide. The disease is characterized by formation of arterial plaques which are mainly comprised of lipids, calcium and in ammatory cells (1) The pathogenesis of CHD is thought to be associated with multifactor, including atherosclerosis, obesity, hypertension, diabetes and smoking habits (2,3). It was reported that in ammatory factors involving cytokines take an essential part in the progression of atherosclerosis, which eventually leads to CHD (4,5).…”
Section: Introductionmentioning
confidence: 99%